The Community Partnership Service Utilization of Social Media for Promoting Binjai Batik Products at UMKM Tan Collection, Binjai District, Binjai City, North Sumatra - Yuyun Yusnida Lase; Andam Lukcyhasnita; Santi Prayudani; Harizahayu; Friendly (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The creative economy serves as a vital platform for promoting and preserving local cultural heritage. UMKM Tan Collection, a creative enterprise producing Binjai's signature "rambutan batik," faces significant marketing challenges as the sole producer of handcrafted rambutan batik in the city. Digital visibility remains particularly low, with minimal online information and motif documentation compared to other batik varieties, resulting in unstable market demand. This community service program aims to enhance the digital promotion and sales of rambutan batik through social media content creation training. The methodology includes problem identification, CapCut video editing workshops, content development assistance, and implementation evaluation. Results demonstrate improved digital literacy among artisans, creation of engaging social media content, and enhanced online brand visibility. The program successfully established a sustainable digital marketing framework, enabling continuous product promotion and cultural preservation through digital platforms.